Design, Synthesis, Pharmacological Evaluation and Descriptor Based Similarities Study of N,N-diphenyl-2-[4-(substituted phenyl)piperazin-1- yl]acetamides as Potential Antipsychotics - Charan Dash, Radha; H. Bhosale, Sharad; M. Shelke, Suhas; R. Suryawanshi, Mugdha; R. Mahadik, Kakasaheb (Medicinal Chemistry, 2012)
A series of novel N,N-diphenyl-2-[4-(substituted phenyl)piperazin-1-yl]acetamides was designed, synthesized and evaluated for anti-dopaminergic activity, anti-serotonergic activity and catalepsy induction studies in mice as an approach to novel potential antipsychotic agent. Antipsychotic activity of these compounds in terms of blocking of dopaminergic transmission was evaluated by their ability to inhibit apomorphine induced climbing behavior in mice and antiserotonergic activity of synthesized compounds was assessed by studying inhibition of 5-HTP induced head twitches. All the synthesized compounds were found to exhibit anti-dopaminergic and anti-serotonergic activity in behavioral models. The compound 3f showed better antipsychotic potential among the different synthesized compounds. The descriptor based similarities study for blood brain permeation established a good similarity between the synthesized compounds with standard atypical antipsychotics.
Keywords: head twitches